Perancangan Aplikasi Kamus Online Informatika-Indonesia Beserta Fungsinya Berbasis Web Menggunakan Metode Sequential Search - Alfira Mahda Ramadini; Apri Junaidi; Fahrudin Mukti Wibowo (Research Group of Data Engineering, Faculty of Informatics, 2021)
In this era of digital optimization, Information and Communication Technology is growing very rapidly. This is in line with the demands and human needs that have been actualized in various fields, such as knowledge and education. To support a learning process based on SCIENCE (Science and Technology) required several supporting aspects such as online dictionary that includes vocabulary and functions of words / terms in the FIELD of IT. One of the supporting aspects is an alternative tool in the form of media that facilitates every community in learning the terms in the field of informatics. According to pie chart data from questionnaires that the authors made, as much as 50 percent of the knowledge of the term informatics of the general public (lay people) can be said to be still very low. In contrast to the academic community such as IT Lecturers and IT Students who do master the field, although it does not close the possibility there are some IT Students who do not fully understand in their fields. The expected result of the authors in this study is the increasing knowledge, especially the general public (lay people) in studying science in the field of IT especially language and informatics terms through online disses. This Online Dictionary application will be designed website-based using sequential search method where sequential search (also called linear search) is the most simple search model performed on a data set. The Online Dictionary application will run by searching for vocabulary or terms in informatics according to the keywords they are looking for, making it easier for users to learn the language of informatics. Keywords: Website, Vocabulary, Dictionary Online, Informatics, IT, Sequential Search, Science and Technology